1968
DOI: 10.2307/3052894
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion and the United States Supreme Court: Mapping of Some Prerequisites for Court Legitimation of Regime Changes

Abstract: Any relatively stable polity must possess means for converting many, if not most, demands made on political authorities into satisfying outputs, whether material or symbolic. Failure to cope with pressing demands might lead to a severely dysfunctional loss of public support for particular officials as well as for the regime itself. On the other hand, efforts to meet demands through blatant violations of accepted rules can also cause great loss in public support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Throughout their lifetime people are socialized to subscribe to the myth of legalism and objectivity (Baird and Gangl 2006;Casey 1974). Combining myth with the public's general ignorance of the judiciary means that people associate courts with characteristics like procedural fairness, legalism, objectivity, and civility in decision-making processes (Casey 1974;Murphy and Tanenhaus 1968;Tyler 1984;Tyler and Rasinski 1991). Given the strong distaste citizens have for the conflicts and compromises intrinsic to the political process (Hibbing and Theiss-Morse 2002), the ability of the courts to shield their inner political workings, or "backstage" areas, from the public is an important factor in maintaining public support (Baird and Gangl 2006;Gibson 2008;Meyrowitz 1985;Lyons 2000, 2001).…”
Section: American Courts and The Mass Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout their lifetime people are socialized to subscribe to the myth of legalism and objectivity (Baird and Gangl 2006;Casey 1974). Combining myth with the public's general ignorance of the judiciary means that people associate courts with characteristics like procedural fairness, legalism, objectivity, and civility in decision-making processes (Casey 1974;Murphy and Tanenhaus 1968;Tyler 1984;Tyler and Rasinski 1991). Given the strong distaste citizens have for the conflicts and compromises intrinsic to the political process (Hibbing and Theiss-Morse 2002), the ability of the courts to shield their inner political workings, or "backstage" areas, from the public is an important factor in maintaining public support (Baird and Gangl 2006;Gibson 2008;Meyrowitz 1985;Lyons 2000, 2001).…”
Section: American Courts and The Mass Mediamentioning
confidence: 99%
“…Research on public opinion toward the U.S. Supreme Court has consistently found a positive relationship between sophistication and diffuse support Casey 1974;Gibson, Caldeira, and Baird 1998;Murphy and Tanenhaus 1968;Scheb and Lyons 2000). That is, "to know the Court is to love it."…”
Section: American Courts and The Mass Mediamentioning
confidence: 99%
“…Early observational studies provided a dismal view of the Supreme Court's role as a leader of mass opinion. Questioning the likelihood of this hypothesis, many pointed to the public's lack of awareness of Court decisions (Adamany 1973;Kessel 1966;Murphy and Tanenhaus 1968). In addition, other conditions for Court-led opinion change have been suggested, including public recognition of the Court's guardian role of the Constitution and public perceptions of competence and impartiality.…”
Section: Can Institutions Move Massmentioning
confidence: 99%
“…In addition, other conditions for Court-led opinion change have been suggested, including public recognition of the Court's guardian role of the Constitution and public perceptions of competence and impartiality. Given that these conditions are rarely fulfilled simultaneously, one would not expect substantial opinion leadership from this perspective (Murphy and Tanenhaus 1968).…”
Section: Can Institutions Move Massmentioning
confidence: 99%
“…Beyond that point, it has been found that the controversial decisions concerning prayer in schools or desegregation have lowered the esteem in which the public holds the Supreme Court (Dolbeare, 1967), but it is not clear from this research whether these changes persist over time or how deeply rooted they are. These public attitudes are directly related to the policy perspectives held by survey respondents in the first place (Murphy & Tannenhaus, 1969). People, then, respond to court decisions based in part on their own personal attitudes concerning the issue in the litigation.…”
Section: Compliancementioning
confidence: 99%